Pengaruh Akuntabilitas, Kompetensi Sumber Daya Manusia dan Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan Blud Puskesmas Se-Kota Metro Lampung - Mirany; Fajar Gustiawaty Dewi; Pigo Nauli (ROE: Research of Economics and Business, 2025)
This study aims to analyze the influence of accountability, human resource competency, and accounting information systems on the quality of the financial reports of Public Health Centers (BLUD) in Metro City. A mixed methods approach was used, with data collection techniques using questionnaires, documentation, and in-depth interviews. Quantitative data were analyzed using multiple linear regression, while qualitative data were analyzed using triangulation and thematic interpretation techniques. The results showed that accountability had no significant effect on the quality of financial reports. Conversely, human resource competency and accounting information systems had a significant and positive influence on the quality of financial reports. This underscores the importance of strengthening the technical capacity of human resources and utilizing technology-based information systems to increase the transparency and reliability of public sector financial reports. This study recommends improving technical training, updating information systems, and strengthening a culture of reporting integrity within the BLUD environment.